Valuing the Great Green Wall economic benefits with the Inclusive Wealth Index approach - Thierry Yerema Coulibaly; Shunsuke Managi (Humanities & Social Sciences Communications)
Abstract Eleven nations launched the Great Green Wall (GGW) initiative to restore 100 million hectares of degraded land in the Sahel by 2030 and combat worsening desertification. However, investment in the initiative has stagnated, and public funding may be necessary. A key barrier to mobilizing such support is the difficulty in comparing the economic benefits of investing in nature against the trade-offs it may pose for other sectors of the economy. This study applies the Inclusive Wealth Index (IWI) framework to assess the net economic value of the GGW. The IWI measures long-term national productivity by accounting for changes in human capital (HC), produced capital (PC), and natural capital (NC). We compare the growth of these assets and overall IWI between GGW and non-GGW countries. Findings show that in 2019, natural capital comprised 19% of Africa’s wealth, down from 31% in 1992. While NC declined in 16 of 40 African countries over this period, HC and PC expanded in all. Between 1990 and 2019, NC grew by 0.1% annually in GGW countries, compared to a −0.06% decline among non-GGW participants. Despite this, IWI growth in GGW countries was 1.3%, substantially lower than the 3.11% observed in other nations. Projections based on historical growth suggest NC could grow by 3.1% if GGW goals are fully met, or by 1.8% if only partially achieved, both significantly higher than business-as-usual trends elsewhere. However, increased investment in NC may reduce growth in HC, PC, and overall IWI for GGW countries. These results underscore that NC investments under the GGW may slow future economic growth unless external funding offsets opportunity costs. There is a need for external funding to balance ecological restoration with sustained economic development.